Empirical Analysis and Realism-Based Flood Mitigation Strategy in Bekasi (case study of eraly march 2025 flood) - Suherman, Anang; Sugandi, Dede; Maryani, Enok (Sumatra Journal of Disaster, Geography and Geography Education, 2025)
Flood is a recurring hydrometeorological disaster in urban areas of Indonesia, including Bekasi City and Regency. This study employs a realism-based geographic approach to analyze the causes, impacts, and formulate mitigation strategies for floods occurring in Bekasi in early March 2025. Using qualitative methods with a case study design, data were collected through observations, interviews, and document studies. The results reveal that floods are caused by a combination of high rainfall intensity, rapid urbanization reducing water catchment areas, poor drainage infrastructure, and topographical vulnerabilities. Beyond physical and economic damages, the disaster severely disrupted educational activities, affecting hundreds of schools and thousands of students. The realism approach highlights the importance of empirical data in understanding flood patterns and designing comprehensive mitigation strategies. Recommended solutions include improving drainage capacity, enforcing land-use regulations, river normalization, and integrating disaster risk reduction (DRR) education into school curricula to build community resilience. This research contributes to evidence-based disaster mitigation efforts in urban planning and education sectors.